Mode 1 Fracture Toughness Of Natural Fibre Reinforced Composites - Nazri, Syaiful Nizam (Universiti Sains Malaysia, 2019)
In general, a composite is a material made from two or more constituent materials of different properties. Nowadays, composites are highly utilized due to its high-performance properties that can be tailored into specified properties such as, high strength-to-weight ratio, wear resistance, corrosion resistance, inflammable properties, and etc. But one of the drawbacks is the cost is expensive. An alternative material for composites is by using natural fibre. Natural fibre reinforced composites constitute a current area of interest in the composite research for polymer composites due to their advantages of being low weight, low cost and environmentally friendly. In this study, the Mode I fracture toughness of the natural fibre reinforced composites will be analysed and evaluated thoroughly. While common mechanical properties of composites such as tensile, compression and flexure were measured in the predecessor studies, this study will focus on the manufacturing, testing and analysis of the stress intensity factor KIC which describes the fracture toughness of the composites. A fabrication method of compression moulding was used to manufacture the specimens for the test and analysis. A Mode I fracture toughness test was carried out by referring to ASTM D5045 standards and procedures. The results from the test were tabulated and plotted into a graph for analysis. The fracture resistance is determined in term of stress intensification factor, KIC. The fracture toughness of the natural fibre reinforced composites shows about the same performance of the conventional composites but with the natural fibre reinforced composites are at a much lower cost.